2016
DOI: 10.1111/jfq.12211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan as an Antifungal and Preservative Agent on Postharvest Blueberry

Abstract: Preventing deterioration and extending shelf life by using natural agents remain challenges in the distribution of premium‐quality blueberry. Herein, Botryotinia fuckeliana (B. fuckeliana) was isolated from the rotting postharvest blueberry and identified, and the causal pathogen was re‐isolated from the decay blueberry to confirm Koch's postulates. Experimental results indicated that spore germination and mycelial growth of B. fuckeliana, were significantly inhibited by chitosan in a concentration‐dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 44 publications
(84 reference statements)
2
25
0
Order By: Relevance
“…Alvarez et al () found significant differences on firmness values when compared fresh and chitosan coated blueberries by a digital penetrometer at initial time of storage. Furthermore, several works on coated blueberries shows a significant improvement on firmness retention and in some cases even an increase of it when this parameter is evaluated in a certain period of time, at a certain storage temperature, and in general by instrumental techniques (Alvarez et al, ; Jiang, Sun, Jia, Wang, & Huang, ; Sun et al, ). Odd‐odor and odd‐flavor were the most affected parameters by the biopreservatives.…”
Section: Resultsmentioning
confidence: 99%
“…Alvarez et al () found significant differences on firmness values when compared fresh and chitosan coated blueberries by a digital penetrometer at initial time of storage. Furthermore, several works on coated blueberries shows a significant improvement on firmness retention and in some cases even an increase of it when this parameter is evaluated in a certain period of time, at a certain storage temperature, and in general by instrumental techniques (Alvarez et al, ; Jiang, Sun, Jia, Wang, & Huang, ; Sun et al, ). Odd‐odor and odd‐flavor were the most affected parameters by the biopreservatives.…”
Section: Resultsmentioning
confidence: 99%
“…According to our previous report (Jiang et al, ), fungal isolation from the lesions was done by transferring a representative portion of decayed blueberry surface‐sterilized with 1% sodium hypochlorite (NaOCl) solution for 2 min and rinsed in sterile distilled water. Fungi were isolated with a sterile scalpel onto PDA plates.…”
Section: Methodsmentioning
confidence: 99%
“…Blueberry is one of the most valuable fruits worldwide because of the potential health benefits and significant economic impact (Giacalone et al, ; Jiang, Sun, Jia, Wang, & Huang, ). However, it is susceptible to several fungal diseases caused by fungi, and it is a serious problem because once blueberries are infected by storage pathogens, the walls of the blueberries soften, while the pathogens will be transmitted intact to adjacent blueberries, leading significant economic loss (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations